Ugly stories of the Peruvian agrarian reform - Mayer, Enrique, 1944- (Latin America otherwise., 2009)
Ugly Stories of the Peruvian Agrarian Reform reveals the human drama behind the radical agrarian reform that unfolded in Peru during the final three decades of the twentieth century. That process began in 1969, when the left-leaning military government implemented a drastic program of land expropriation. Seized lands were turned into worker-managed cooperatives. After those cooperatives began to falter and the country returned to civilian rule in the 1980s, members distributed the land among themselves. In 1995-96, as the agrarian reform process was winding down and neoliberal policies were undoing leftist reforms, the Peruvian anthropologist Enrique Mayer traveled throughout the country, interviewing people who had lived through the most tumultuous years of agrarian reform, recording their memories and their stories. While agrarian reform caused enormous upheaval, controversy, and disappointment, it did succeed in breaking up the unjust and oppressive hacienda system. Mayer contends that the demise of that system is as important as the liberation of slaves in the Americas.